Research on the reflection of cultural dimensions in international business - Edita Leonavičienė; Aurelija Burinskienė (Insights into Regional Development)
The objective of this research is to reveal the reflection of cultural dimensions in international business. The management of an international business is complex and varies according to culturally determined values. To achieve success in international business, it is necessary to understand how cultural differences across and within countries affect it. Authors took under revision the international companies listed under the Nasdaq database (2021) and researched interlinks in the North-West region of Europe. The authors delivered the research in two stages. In the first stage, the authors constructed a matrix of cultural dimensions. Then formed the equation at the second step by using the Generalized Moments Method, which eliminates inaccurate assumptions. The authors used panel data analysis and constructed equations. The theoretical research results highlight the cultural dimensions identified in the 31 studies in the priority of attention. The authors' research proves that three main cultural dimensions affect the revenue of the international business. We came to the insight that the impact of culture in doing business globally is growing rapidly.